PENGARUH KOMITMEN KERJA, KETERAMPILAN PEKERJA DAN DISIPLIN KERJA TERHADAP PENCAPAIAN TARGET PERUSAHAAN - Muhammad Azizulhaq; Dicky Jhoansyah; Faizal Mulia Z (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of work commitment, workers’ skills, and work discipline on the achievement of company targets among project workers at CV. Adilia, Sukabumi City, a company operating in the construction sector. The research is motivated by field findings indicating delays in project completion compared to planned targets, caused by several factors such as weak commitment to schedules, limited availability of skilled workers, and insufficient work discipline. This research employed a quantitative approach using a saturated sampling technique, in which all 36 project workers were selected as respondents. Data were collected through a Likert-scale questionnaire and analyzed using SPSS version 29, including validity testing, reliability testing, classical assumption tests, and multiple linear regression analysis. The results showed that all questionnaire items were valid and the research instrument was reliable (Cronbach’s Alpha > 0.70). The simultaneous test (F-test) demonstrated that work commitment, workers’ skills, and work discipline jointly have a significant effect on the achievement of company targets, with a multiple correlation coefficient of 0.898 and a coefficient of determination of 80.6%. However, the partial test (t-test) revealed that only work commitment has a significant effect, while workers’ skills and work discipline do not have a significant influence individually. This study recommends that the company strengthen employees’ work commitment through motivation, open communication, and reward systems, while continuing to provide skill development programs and implementing consistent work discipline to support long-term project performance.